2014
DOI: 10.3389/fgene.2014.00366
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanisms of human RecQ helicases WRN and BLM

Abstract: The RecQ family DNA helicases Werner syndrome protein (WRN) and Bloom syndrome protein (BLM) play a key role in protecting the genome against deleterious changes. In humans, mutations in these proteins lead to rare genetic diseases associated with cancer predisposition and accelerated aging. WRN and BLM are distinguished from other helicases by possessing signature tandem domains toward the C terminus, referred to as the RecQ C-terminal (RQC) and helicase-and-ribonuclease D-C-terminal (HRDC) domains. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 74 publications
(170 reference statements)
1
58
1
Order By: Relevance
“…S8). These findings raise the possibility that the HRDC-motor core interaction stabilizes the helicase in a configuration specific for invasion disruption (36) (Fig. 4B).…”
Section: Discussionmentioning
confidence: 85%
“…S8). These findings raise the possibility that the HRDC-motor core interaction stabilizes the helicase in a configuration specific for invasion disruption (36) (Fig. 4B).…”
Section: Discussionmentioning
confidence: 85%
“…Although the WRN and the BLM helicases belong both to the family of RecQ helicases, defects of either during DSB response may lead to opposing outcomes [Suhasini and Brosh, 2013;Croteau et al, 2014;Keijzers et al, 2014;Kitano, 2014]. Loss of WRN is associated with a variegated translocation mosaicism and a reduction in DNA recombination [Salk et al, 1981;Dhillon et al, 2007;Melcher et al, 2000].…”
Section: Genes and Proteinsmentioning
confidence: 99%
“…Our results demonstrate that the HRDC domain also plays a critical role in strand synthesis across the telomeric G-rich repeats in vitro and contributes to telomere length homeostasis in vivo. The HRDC domain is conserved among many RecQ helicases and is thought to mediate protein interactions and DNA binding (5). Interestingly, a recent study has shown that the HRDC domain of BLM interacts with the single-stranded DNA ahead of G4 DNA and cooperates with helicase activity to unwind these DNA structures (60).…”
Section: Discussionmentioning
confidence: 99%